Penegakan Hukum terhadap Tindak Pidana Main Hakim Sendiri (Eigenrichting) Yang Dilakukan oleh Masyarakat di Wilayah Hukum Kepolisian Resor Malaka 2019-2023 - Gilberth Brechmans Julyan Kugu; Debi F. Ng. Falo; Deddy R. Ch. Manafe (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to analyze law enforcement against the crime of vigilantism (eigenrichting) committed by the community in the jurisdiction of the Malacca Resort Police 2019-2023. This research uses empirical legal research, where primary data is obtained through interviews and documentation at the Malacca Police Office, while secondary data is obtained through literature study. The author is interested in conducting research related to this issue because in Malacca district vigilantism occurs quite often, the proof is that in 2019 there were 1 case, in 2020 there were 3 cases, in 2021 there were 3 cases, in 2022 there were 6 cases, and in 2023 there were 2 cases. In this study, it was found that. There are several efforts made by the police, including repressive, preventive, pre-emtif efforts. And there are also other efforts made by the Malacca Police in handling the crime of vigilantism (eigenrichting) committed by the community in the Malacca Police jurisdiction, namely providing socialization about the law to the community, preventing the sale of alcohol, carrying out routine patrols. Then the following main problem is that in the efforts of the Malacca Police in handling vigilante crimes there are several factors, namely supporting and inhibiting factors. Supporting factors in the investigation and investigation of vigilante crimes (Eigenrichting) at Malacca Police Station Supporting factors include community involvement that provides important information to the police in revealing suspected criminal acts in the area and also internal support and external support. However, there are also inhibiting factors such as the distance between Malacca Police Station, the Court, and the Prosecutor's Office, the lack of knowledge about the law among the community, and the lack of public awareness of the obligation to comply with the law, which causes repeated violations of the law.